A Novel Algorithm in the Management of Hypoglycemia in Newborns. (12th November 2014) - Naveen, Swapna; Rosy, Chikati; Kandraju, Hemasree; Sharma, Deepak; Oleti, Tejopratap; Murki, Srinivas
Abstract : Study Objective . To evaluate the safety of a new protocol in comparison to the standard protocol for managing hypoglycemia in neonates. Methods . Open label RCT-pilot study. Neonates admitted to NICU with hypoglycemia and requiring intravenous fluids were included. Fifty-seven eligible neonates were randomly allocated to either intervention group (starting fluids with 10% dextrose and increments of 1.5%) or standard protocol group (GIR of 6 mg/kg/min with increments of 2 mg/kg/min) till control of hypoglycemia. Primary outcome of the study was to know proportion of infants with subsequent hypoglycemia and hyperglycemia after enrolment. Results . The initial GIR (6 ± 0 mg/kg/min versus 4.8 ± 1.4 mg/kg/min, P < 0.001), the mean maximum GIR (6.7 ± 1.6 mg/kg/min versus 5.6 ± 2 mg/kg/min, P = 0.03), the maximum concentration of glucose infused (13.8 ± 2.9% versus 10.9 ± 1.9%, P < 0.001), and the total amount of glucose infused were significantly lower in the intervention group. The mean maximum blood sugar was significantly higher (129 ± 57 mg/dL versus 87 ± 30 mg/dL, P = 0.001) and there was a trend towards high proportion of infants with Hyperglycemia in the standard protocol group ( n = 10, 39% versus n = 5, 16%, P = 0.07). The median difference between the highest and the lowest recorded sugar for any infant was significantly higher in the standard protocol group (median 93 mg/dL, IQR 52 to 147 mg/dL versus median 50 mg/dL, IQR 38 to 62.5 mg/dL, P = 0.03). Conclusion . A new and novel algorithm in the management of hypoglycemia in neonates is as safe as the standard protocol and requires further testing before routine implementation.